The Purpose of Teaching Young Adult Literature in Secondary Education: Focus on Poverty, Gender and Sexuality - Darshana Chakrabarty (Universitas Teuku Umar, 2020)
Although Young Adult literature has been around for quite some time, it has never been viewed or considered to be fit to teach in a classroom setting, as it was poles apart from classics. Young Adult Literature deals with current social, economic, political as well as personal issues relating to and addressing a particular group of people, the young adults. Taking the themes ‘Poverty and Privilege’ and ‘Gender and Sexuality’, this article discusses the purpose of Young Adult Literature in school curriculum and the methods of teaching them to students to spread awareness and help in shaping conscious citizens of the world. The themes and issues of the books ‘The House on Mango Street’, ‘Hey Kiddo’, ‘If You Could Be Mine’ and ‘Some Assembly Required: The Not-So-Secret Life of a Transgender Teen’ and the reason for teaching them in schools are explored in detail in the hope of shedding light on the darker aspects of life.